2007
DOI: 10.1111/j.1464-5491.2007.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

When is a technically successful peripheral angioplasty effective in preventing above‐the‐ankle amputation in diabetic patients with critical limb ischaemia?

Abstract: In patients with diabetes, PTA is effective in avoiding major amputation, provided recanalization occurs in at least one tibial artery down to the foot. In a few patients, re-canalization of the peroneal artery alone is not sufficient to avoid major amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 28 publications
2
52
0
7
Order By: Relevance
“…It is equally clear, however, that it is irrelevant to major amputation: at 30 days none of the patients with CLI needed major amputation, and also in the longer follow-up the percentages of participants requiring major amputation were equal. This confirms that revascularisation of at least one artery of the foot is effective in avoiding major amputation in the neuropathic patient [28]. Therefore, both Goldenberg et al [25] and LoGerfo and Coffman [24] were right: Goldenberg et al actually saw arteriolar occlusive disease and LoGerfo and Coffman showed that revascularisation was effective in preventing amputation.…”
Section: Discussionmentioning
confidence: 51%
“…It is equally clear, however, that it is irrelevant to major amputation: at 30 days none of the patients with CLI needed major amputation, and also in the longer follow-up the percentages of participants requiring major amputation were equal. This confirms that revascularisation of at least one artery of the foot is effective in avoiding major amputation in the neuropathic patient [28]. Therefore, both Goldenberg et al [25] and LoGerfo and Coffman [24] were right: Goldenberg et al actually saw arteriolar occlusive disease and LoGerfo and Coffman showed that revascularisation was effective in preventing amputation.…”
Section: Discussionmentioning
confidence: 51%
“…PTA has established itself as a first-line treatment for CLI in patients with diabetic foot, with similar results to surgery in terms of limb salvage and patency [8][9][10]. The main studies in the literature [13,16,[23][24][25][26][27][28][29][30] reported, for endovascular treatment, a technical success rate of about 90 %, a negligible mortality rate, and a limb salvage rate at 3-5 years of 72-98 %.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of PTA treatment is to restore the patency of at least one below-the-knee (BTK) vessel, preferably the tributary of the anatomical region of the ulcer [9]. Several studies have demonstrated good results in terms of patency and limb salvage after endovascular treatment of diabetic foot [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They introduced a simple concept: one patent vessel could be enough, but two patent vessels are better than one and three patent vessels are better than two. Moreover, the patency of the tibial vessels seems to be more important than that of the peroneal artery [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular therapy with drug-eluting devices has recently been gaining more and more success in different vascular districts as well as in the below-the-knee region [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%